IN VITRO ANTIOXIDANT AND IN VIVO HEPATOPROTECTIVE ACTIVITY OF LEAVE EXTRACT OF RAPHANUS SATIVUS IN RATS USING CCL4 MODEL - Syed, Shariq Naeem; Rizvi, Waseem; Kumar, Anil; Aijaz, Khan Ahmad; Shagufta, Moin; Akif, Ahsan (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Raphanus sativus is reported to have a variety of biological activities. This work screened the hepato-protective and antioxidant activity of ethanol (ERS), and aqueous (ARS), extracts of leaves of Raphanus sativus in Carbon tetrachloride (CCl4), model in rats. Material and Methods: The extracts were subjected to antioxidant tests (Total reducing power and Total phenolic content), and preliminary phytochemical screening. A pilot study was done on 100 and 300 mg/kg extracts, form which 300 mg was chosen for further experiments. The albino rats (200-250 grams), were divided into 5 groups of 6 animals each (n=6). There were three control groups comprising of normal control (normal saline -1ml/kg), negative control group (CCl4 1ml/kg in olive oil in a ratio of 1:1 v/v), and positive control group (Silymarin 50mg/kg). The Test drugs were given in a dose of 300 mg/kg for both ERS and ARS extract for 7 days. Biochemical parameters (AST, ALT, Alkaline phosphatase, Total Bilirubin), histo-pathological examination of liver and in vivo antioxidant tests [CAT, GSH and MDA] were done.Results: The phytochemical study showed the presence of flavanoids, terpenoids, alkaloids, saponins and sterols. A dose dependent increase in the oxidative potential was observed in both the extracts with total phenolic content 70.1 and 44.4 GAE/g extract for ERS and ARS respectively. ERS 300mg/kg showed a significant (p<0.001) increase in levels of AST, ALT and alkaline phosphatase as compared to negative control (percentage hepatoprotection =45.3%) while ARS 300 mg/kg (p<.01) group showed 30% hepatoprotection. The GSH (p<0.001) and CAT (p<0.05) in ERS and ARS were significantly increased while MDA levels were decreased (P< 0.01), as compared negative control. The findings were confirmed histo-pathological examination. Conclusion: The ethanol and aqueous extract of Raphanus sativus have partial hepatoprotection against CCl4 toxicity.